The positions of the scholars of hadith and scientists that used ijtihad (The comparative analisis - Aдилбaевa Ш. (Journal of Oriental Studies, 2017)
The method used by the Prophet Muhammad and his sahabas’ during their lifetimes is called “roy” which means “the final decision, the opinion, which could come after reflection, meditation and much effort on finding the right solution”.It was also used during Taabi’een and by Hadith scholars and “Ashab-roy”. However, despite this, pointing out that the debate continued, these differences resulted in the fact that the Hijaz school was related to Hadith scholars and Iraqi school - to “Ashab-roy.” The existence of these two schools is a historical fact. However, this classification does not correspond to the scientific truth. In the article the Islamic scientists which are called scholars of hadith and scientists that used ijtihad are considered.